Bamboo torrefaction in a high gravity (Higee) environment using a rotating packed bed - Pillejera, Ma. Katreena V.
Torrefaction of raw bamboo (Phyllostachys mankinoi) in a high gravity (Higee) environment is investigated. A rotating packed bed (RPB) is used and three rotating speeds of 0,900, and 1800 rpm, corresponding to the mean centrifugal forces of 0,58, and 234 g, are taken into account. The results suggest that the Higee environments intensify the torrefaction performance drastically when the operations of light (206°C) and mild (255°C) torrefaction are practiced, stemming from the enhancement of heat and mass transfer in the rotating bed. In contrast, the torrefaction performance is affected slightly by the rotating speed when severe torrefaction (300°C) is carried out. With the torrefaction conditions of 300 °C and 1800 rpm, the highest HHV (28.389 MJ/kg) with and HHV enhancement factor (EF) of 1.61 is obtained, yielding a coal-like fuel,and energy yield is 63.51%. The torrefaction operation at 255°C and 1800 rpm for 30 min upgrades the bamboo with EF (1.53), HHV (26.988 MJ/kg), and energy yield (65.21%) values, which is close to the torrefied biomass under the most severe torrefaction conditions, and is thus recommended. The results suggested that torrefaction in a Higee environment is a promising process for upgrading biomass to produce carbon-neutral fuel utilized in industry.